"Juara" vs. "champion": translation of cultural elements - Rashid Ali, Farrah Diebaa (IIUM Press, 2017)
Culturally-embedded word is a major setback for translators as different societies have their own distinct culture. Thus a translator is obliged to adopt a few techniques in order to accommodate these problems. This study investigated the translation techniques used in capturing the essence of culturally-embedded expression in the English version of the novel ‘Juara’. It was done through textual analysis and the findings were presented quantitatively. Findings of this research suggested that even though there was a strong relationship between cultural elements and translation techniques presented in the text, it was difficult to associate each cultural element to a specific technique.